Giant Temporal Bone Angiosarcoma: Case Report and Literature Review - Finger, Guilherme; Godoy, Bruno Loyola; Silva, Bruna Koeche da; Pessôa, Carolina Fittipaldi; Souto, Antonio Aversa do (Arquivos Brasileiros de Neurocirurgia: Brazilian Neurosurgery, 2022)
The authors describe a very rare case of an angiosarcoma originating from the petrous portion of the temporal bone that evolved as an indolent lesion until it became a giant retroauricular mass. A biopsy demonstrated that it was an angiosarcoma. A presurgical embolization from the left occipital and left parietal branches of the left middle meningeal artery was performed, followed by a total resection of the tumor. The patient developed a transient dysphasia during early follow-up, from which, subsequently, she fully recovered. There were no signs of recurrence in the current 3 years of follow-up. Free margins can be achieved even in some giant tumors and remain the most important prognostic factor for soft tissue malignant tumors with intracranial infiltration.
Keywords: sarcoma; skull base; temporal bone; case report